Farnesylation of human guanylate‐binding protein 1 as safety mechanism preventing structural rearrangements and uninduced dimerization. (31st July 2019) - Lorenz, Charlotte; Ince, Semra; Zhang, Tao; Cousin, Anneliese; Batra‐Safferling, Renu; Nagel‐Steger, Luitgard; Herrmann, Christian; Stadler, Andreas M.
Abstract : Human guanylate‐binding protein 1 (hGBP1) belongs to the family of dynamin‐like proteins and is activated by addition of nucleotides, leading to protein oligomerization and stimulated GTPase activity. In vivo, hGBP1 is post‐translationally modified by attachment of a farnesyl group yielding farn‐hGBP1. In this study, hydrodynamic differences in farn‐hGBP1 and unmodified hGBP1 were investigated using dynamic light scattering (DLS), analytical ultracentrifugation (AUC) and analytical size‐exclusion chromatography (SEC). In addition, we performed small‐angle X‐ray scattering (SAXS) experiments coupled with a SEC setup (SEC‐SAXS) to investigate structural properties of nonmodified hGBP1 and farn‐hGBP1 in solution. SEC‐SAXS measurements revealed that farnesylation keeps hGBP1 in its inactive monomeric and crystal‐like conformation in nucleotide‐free solution, whereas unmodified hGBP1 forms a monomer–dimer equilibrium both in the inactive ground state in nucleotide‐free solution as well as in the activated state that is trapped by addition of the nonhydrolysable GTP analogue GppNHp. Nonmodified hGBP1 is structurally perturbed as compared to farn‐hGBP. In particular, GppNHp binding leads to large structural rearrangements and higher conformational flexibility of the monomer and the dimer. Structural changes observed in the nonmodified protein are prerequisites for further oligomer assemblies of farn‐hGBP1 that occur in the presence of nucleotides. Database: All SEC‐SAXS data, corresponding fits to the data and structural models are deposited in the Small Angle Scattering Biological Data Bank [SASBDB ( Nucleic Acids Res, 43, 2015, D357)] with project IDs: SASDEE8, SASDEF8, SASDEG8, SASDEH8, SASDEJ8, SASDEK8, SASDEL8 and SASDEM8. Abstract : Human guanylate‐binding protein 1 (hGBP1) is activated by the addition of nucleotides, which leads to protein oligomerization and stimulated GTPase activity. Earlier studies focused on the unmodified protein, although in vivo hGBP1 is farnesylated. We studied the effect of farnesylation using a combination of different biophysical methods, which revealed that farnesylation is needed to lock the protein in an inactive monomeric state, perhaps as a safety mechanism.